Evaluation of Physician Compliance in the Implementation of Clinical Pathways at Moh Ridwan Meuraksa Level Ii Hospital Jakarta - Ahyaita, Ahyaita; Wahyudi, Bayu; Andikarya, Oke (Research of Service Administration Health and Sains Healthys, 2026)
This study aims to evaluate the level of physician compliance in the implementation of Clinical Pathways (CP) at Moh Ridwan Meuraksa Class II Hospital, Jakarta. Clinical Pathways function as a clinical care management tool designed to ensure consistency, efficiency, and quality of patient services based on scientific evidence and standardized procedures. The research applied a quantitative approach with an observational cross-sectional design through direct observation and the distribution of questionnaires to physicians. The sample consisted of 40 physicians involved in the implementation of CP for five major diagnoses, namely Acute Myocardial Infarction (AMI), Severe Preeclampsia, Hypertrophic Tonsils, Femur Fracture, and Cervical Cancer. The research instruments included observation sheets and questionnaires that had been tested for validity (r > 0.361) and reliability (Cronbach’s Alpha = 0.857). The findings indicate that overall physician compliance with CP implementation falls into the moderate category (65.8%). The highest compliance occurred in emergency clinical examinations and initial therapy administration, while the lowest compliance appeared in variance documentation and multidisciplinary consultation. The study recommends strengthening training, improving information systems, and integrating CP into Electronic Medical Records to enhance compliance and service quality.